2017
DOI: 10.1007/s00168-017-0841-6
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and regional economic resilience: an exploratory analysis

Abstract: The varying rates of recovery of European regional economies from the 2007 to 2008 economic crisis have raised interesting questions about the sources of economic resilience. Policy discourse has increasingly asserted the role played by innovation in facilitating rapid recovery from economic shocks, whilst evolutionary thinking has highlighted the specific importance of innovation capacity. However, empirical evidence on this is lacking. This paper addresses this gap by providing new empirical analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
160
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(170 citation statements)
references
References 47 publications
5
160
0
5
Order By: Relevance
“…Looking at the most downloaded papers, we see that the majority of the papers (3 out of 5) deals with the topic of resilience (Bristow and Healy 2018;Kitsos and Bishop 2018;Di Caro and Fratesi 2018). There are at least two explanations for this.…”
Section: Continued Broad Range Of Topics In Published Papersmentioning
confidence: 97%
“…Looking at the most downloaded papers, we see that the majority of the papers (3 out of 5) deals with the topic of resilience (Bristow and Healy 2018;Kitsos and Bishop 2018;Di Caro and Fratesi 2018). There are at least two explanations for this.…”
Section: Continued Broad Range Of Topics In Published Papersmentioning
confidence: 97%
“…Boschma () overcomes this ambiguity by suggesting the important role that related and unrelated variety can play in promoting resilience, particularly the transformation of the economy towards new development paths (see also Xiao et al, ). Other authors have emphasized the importance of innovation, and creativity more generally, in promoting the resilience of economies to economic shocks (Bristow & Healy, ; Cavaco & Machado, ; Crescenzi & Rodríguez‐Pose, ; Pinto & Pereira, ), which speaks to the adaptive theme of resilience. In a similar vein, others identify the important role that skills and higher levels of human capital can play in promoting resilient economies (Polèse, ), as well as the positive role that foreign direct investment (FDI) is suggested to play (Bristow et al, ).…”
Section: Resilience and Varieties Of Capitalismmentioning
confidence: 99%
“…Martin, Sunley, Gardiner, and Tyler () found that economic structure has an influence on resilience but that many other “region‐specific” factors are prominent, including the relative importance of small enterprises, the degree of foreign ownership of local industry, export orientation, as well as institutional conditions. Innovation was found to play a key role by Bristow and Healey's () study on the response of European regional economies to the 2007 crisis. They found that regions identified as innovation leaders were more likely to have either resisted the crisis or recovered quickly from it.…”
Section: Innovation In the Economic Downturnmentioning
confidence: 99%
“…As suggested by Bristow and Healey (), socio‐economic resilience, in particular of regions, is crucially connected to firms' innovation capacity and therefore highly dependent on learning processes associated with knowledge. The distinction between exploration—knowledge development—and exploitation—knowledge use—can be here particularly useful (Levinthal & March, ; Winter, ).…”
Section: Innovation In the Economic Downturnmentioning
confidence: 99%